An algebra problem by Mehul Chaturvedi

Algebra Level 4

Let f ( x ) = x 3 + a x 2 + b x + c f(x)=x^3+ax^2+bx+c and g ( x ) = x 3 + b x 2 + c x + a , g(x)=x^3+bx^2+cx+a, where a , b , c a,b,c are integers with c 0. c\neq0. Suppose that the following conditions hold:

(i) f ( 1 ) = 0 ; f(1)=0;

(ii) the roots of g ( x ) = 0 g(x)=0 are the squares of the roots of f ( x ) = 0. f(x)=0.

Find the value of a 2013 + b 2013 + c 2013 . a^{2013}+b^{2013}+c^{2013}.


The answer is -1.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Chew-Seong Cheong
Oct 24, 2014

Let the roots of f ( x ) f(x) be α \alpha , β \beta and γ \gamma , then those of g ( x ) g(x) are α 2 \alpha^2 , β 2 \beta^2 and γ 2 \gamma^2 .

Since α β γ = c \quad \alpha \beta \gamma = -c \quad and α 2 β 2 γ 2 = a a = c 2 \quad \alpha^2 \beta^2 \gamma^2 = -a \quad \Rightarrow a = -c^2 .

Also α 2 + β 2 + γ 2 = ( α + β + γ ) 2 2 ( α β + β γ + γ α ) \quad \alpha^2 + \beta^2 + \gamma^2 = (\alpha + \beta + \gamma)^2 - 2( \alpha \beta + \beta \gamma + \gamma \alpha)

b = a 2 2 b b = a 2 = c 4 \Rightarrow -b = a^2 - 2b\quad \Rightarrow b = a^2 = c^4

Now f ( 1 ) = 1 + a + b + c = 0 c 4 c 2 + c + 1 = 0 \quad f(1) = 1 + a + b + c = 0\quad \Rightarrow c^4 - c^2 + c +1 = 0

c = 1 \Rightarrow c = -1 , a = 1 a = -1 and b = 1 b = 1

a 2013 + b 2013 + c 2013 = 1 + 1 1 = 1 \Rightarrow a^{2013} + b^{2013} + c^{2013} = -1+1-1=\boxed {-1} .

Mayank Singh
Apr 3, 2015

As far as I remember, that's an R.M.O. question

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...